Quantitative Portfolio Management Through Carbon Budgeting in a PSX Perspective - Muhammad Irfan Majeed; Unbreen Arif; Adnan Hushmat (Indonesian Journal of Sustainability Accounting and Management, 2022)
Portfolio management requires investment managers to consider investor preferences before taking any investment decisions. Some of the investors might be interested in building a clean, environmentally friendly, and carbon-free portfolio, assuming it as their corporate social responsibility (CSR) or owing to some fear of future loss arising from the ban on environment-hampering companies that might not be following the environmental, social, and governance (ESG) requirements. Historically, we have seen a ban on Chinese products because of the issues of carbon emissions. Similarly, during SMOG, many brick kilns and iron foundries are closed in Pakistan every year. The carbon budgeting on the portfolio can help achieve the CSR and sustainability goals of investors. The study attempts to develop a portfolio based on historical data, which could yield optimum results while remaining carbon conscious. The study aims to find the best-performing portfolio that could be more ESG compliant and may achieve CSR objectives to protect the environment and investors’ interests simultaneously. The findings show that companies segregated based on carbon footprint can create a carbon-free portfolio (approximately 25%) without a material impact on the expected risk and return profile. To be more ESG compliant, an investor can compromise slightly on returns, that is, only compromising 3% of the profit, we can maintain a 50% compliant portfolio in Pakistan’s environment. The study tries to improve the understanding of regulatory requirements but would also help us gain the confidence of investors who are keen to see carbon-free portfolios or in other words want to ensure investments in environmentally friendly industries.